Developing PjBL-Based Google Sites Teaching Materials for Advertising, Slogans, and Posters to Enhance Students’ Conceptual Understanding and Creativity - Ayu Asih Sulistiyorini; Tri Suminar; Amin Yusuf; Moses Adeleke Adeoye (Universitas Negeri Semarang, 2026)
The Merdeka Curriculum is an educational innovation that provides flexibility for schools and teachers to develop learning that is relevant to students' needs. However, the implementation of the Merdeka Curriculum in SKB Semarang Regency faces the challenge of students' low understanding of concepts and creativity, especially in advertising materials, slogans and posters. To overcome this problem, this research aims to develop teaching-based materials Google Sites with models Project-Based Learning (PjBL) which is effective in increasing students' conceptual understanding and creativity. This research uses research and development methods (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection was carried out through interviews, questionnaires and observations. This research shows that teaching materials are based Google Sites developed meets the criteria of validity, practicality and effectiveness. Expert validation gave an average score of 90.83%, which indicates that this teaching material is very suitable for use. Statistical tests showed a significant increase in students' conceptual understanding and creativity, with the average posttest score for the experimental class being higher than the control class. Based teaching materials Google Sites This not only improves understanding of concepts, but also encourages active involvement of students through creative projects that are relevant to the real world. Application of based technology Google Sites allows more flexible learning, especially for students with limited time, such as student workers in the package pursuit program. The novelty of this research lies in the integration of the model Project-Based Learning with Google Sites which is designed to improve interactive learning in the context of the Independent Curriculum. This approach supports the development of students' creativity through project exploration that is contextual and based on real needs. This research is an important reference for the development of digital teaching materials at various levels of education. Use of technology Google Sites not only provides flexibility in learning access, but also encourages learning that is more interactive, creative, and in accordance with the principles of the Independent Curriculum. Thus, teaching materials are based Google Sites which was developed into an innovative solution to improve the quality of learning